Students’ Perception towards Collaborative Learning’s Contribution to Students’ Active Participation in ELT Class - Fatima, Fatima; Rengur, Zul Aini; Mansur, Nurfauziah (Yayasan Pendidikan Bima Berilmu, 2024)
Collaborative Learning replacing the passive learning paradigm with a proactive and interactive model. It is has been implemented in the learning process by educators, starting from beginner level to the university level. This research intended to explore the students’ perception toward collaborative learning’ contribution to their active participation in the learning process. A mixed method approach was employed in this research with the explanatory sequential mixed methods design. The quantitative data were gathered from the questionnaire that was distributed to 74 students of English Tadris Study Program at UIN Datokarama Palu, while the qualitative data were gathered from the interview. The findings revealed that the students give a positive reaction to the contribution of CL implementation in promoting their active engagement in the learning process. The students’ active participation in the learning process was demonstrated in three points. First, collaborative learning enhanced the students’ interaction with their peers in the learning process. Second, collaborative learning encouraged the students’ engagement. Finally, collaborative activities promoted students to generate ideas.